Thermoregulatory role of insensible evaporative water loss constancy in a heterothermic marsupial - Cooper, Christine; Withers, Philip (Royal Society Publishing, 2017)
© 2017 The Author(s). 'Insensible' evaporative water loss of mammals has been traditionally viewed as a passive process, but recent studies suggest that insensible water loss is under regulatory control, although the physiological role of this control is unclear. We test the hypothesis that regulation of insensible water loss has a thermoregulatory function by quantifying for the first time evaporative water loss control, along with metabolic rate and body temperature, of a heterothermic mammal during normothermia and torpor. Evaporative water loss was independent of ambient relative humidity at ambient temperatures of 20 and 30°C, but not at 25°C or during torpor at 20°C. Evaporative water loss per water vapour pressure deficit had a positive linear relationship with relative humidity at ambient temperatures of 20 and 30°C, but not at 25°C or during torpor at 20 or 25°C. These findings suggest that insensible water loss deviates from a physical model only during thermoregulation, providing support for the hypothesis that regulation of insensible evaporative water loss has a thermoregulatory role.